RURAL DEVELOPMENT BY WATER CONSERVATION - Manjulakar B.H; Bansode I.B.; Budhale A.S; Hadare S.S (Research Parks Publishers, 2020)
The water conservation measure has been suggested on the Piyali River basin area in Kultali Block of South 24th Parganas, West Bengal, India for rainwater harvesting based on field survey. In this study, the Basin of Piyali River, an estuarine river with regular tidal influx, with special emphasis on Kultali Block has been chosen for utilizing the water of the Piyali River during dry months and augmenting water supply through rainwater harvesting in the Kultali Block mouza-wise. Especially during flash floods the entire catchments used to be flooded. To eradicate the problem, in early post-independence time a master plan was prepared and implemented by the Irrigation Department to restrict the entry of tidal ingress by means of a major sluice gate and construction of similar sluices in each tributaries debouching to the Piyali River, to check the flood problem in the area as also to conserve rainwater for use in the lean periods. Unfortunately after thirty years of installation of the closure, the Piyali River remains saline during dry months thereby defeating the very important purpose of utilizing huge quantum of water for irrigation during dry months of the year. Consequently the present study suggests some measure to eradicate the salinity problem in the river. An extensive plan has been made on the basis of study for augmenting water supply through rain water harvesting with the help of ponds network. The measure needs to be implemented for irrigation facilities for multi cropping in the area of Kultali Block to make the water of Piyali River fresh. Thus the main objective is to provide a plan for augmenting irrigation water for the development of command area by considering either of individual land or community land block wise through rainwater harvesting structure ponds and also to suggest crop pattern and crop rotation according to water availability, quality and soil condition. The study attempts to delineate not only for enhancement of their economic return through pisciculture and improved cropping intensity during dry season for sustaining their livelihood but also reducing the salinity level of the Piyali River by selecting the location of the dyke in Piyali River for utilizing huge quantity of water for multi-cropping during lean period..